The Effect of Current Inhomogeneity on the Performance and Degradation of Li-S Batteries. Issue 1 (29th November 2017) - Hunt, I.; Zhang, T.; Patel, Y.; Marinescu, M.; Purkayastha, R.; Kovacik, P.; Walus, S.; Swiatek, A.; Offer, G. J.
Abstract : The effect of thermal gradients on the performance and cycle life of Li-S batteries is studied using bespoke single-layer Li-S cells, with isothermal boundary conditions maintained by Peltier elements. A temperature difference is shown to cause significant current imbalance between parallel connected single-layer cells, causing the hotter cell to provide more charge and discharge capacities during cycling. During charge, significant shuttle is induced in the hotter Li-S cell, causing accelerated degradation of it. A bespoke multi-tab cell in which the inner layers are electrically connected to different tabs versus the outer layers, is used to demonstrate that noticeable current inhomogeneity occurs during the operation of practical multilayer Li-S pouch cells, which is expected to affect their performance and degradation. The observed thermal and current inhomogeneity should have a direct consequence on battery pack and thermal management system design for real world Li-S battery packs.